Numerical Analysis of Crack Propagation Path Using an Advanced Element Cracking Method - Zhong, Z.P.; Wan, S.; Jiang, Z.W. (Проблемы прочности, 2014)
The determination of the crack path is important for predicting the unexpected failures or assessing fatigue life in engineering material. To simulate the crack path under mixed mode loading using a finite element model, a new local element cracking technique was proposed. The waiting cracking element was divided into two units along crack propagation direction based on the maximum circumference ( 0) KII criterion. Then, the information of element number and nodal number was also modified and singular elements were avoided by the transfixion method. With advantages of small remeshing only on a local region, this method also examined three classic problems of stationary crack growth, i.e., edge crack propagation in double cantilever beam, mode I cracking in an asphalt concrete beam, a crack in typical longitudinal connection of large natural gas carriers. The calculated stress intensity factors and the predicted crack trajectories using this method agree well with the theoretical solutions existing in literature. Optimal design of structure against failure by fast fracture is discussed.